Fabry disease – what a gastroenterologist should know - Alicja Rydzewska-Rosołowska; Tomasz Hryszko (Gastroenterology Review)
Fabry disease is a rare, X-linked metabolic error caused by various mutations in the -galactosidase A gene, which results in the accumulation of glycosphingolipids. Gastrointestinal symptoms are quite common in affected patients; therefore, it is important for gastroenterologists to keep it in mind as a differential diagnosis for especially challenging patients. The following review provides concise information on epidemiology and genetics, signs, and symptoms of the disease, focusing on the gastrointestinal (GI) tract, providing a brief overview of the diagnostic process and the available treatment, both disease specific and supportive, again with a focus on alleviation of gastrointestinal symptoms.